2003
DOI: 10.1046/j.1365-2893.2003.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower expression of CD81 B‐cell receptor in lymphoproliferative diseases associated with hepatitis C virus infection

Abstract: Chronic hepatitis C virus (HCV) infection is frequently associated with type II mixed cryoglobulinaemia (MC), a benign lymphoproliferative disease (LPD). More recently, HCV has been implicated as a possible aetiologic factor of B-cell non-Hodgkin lymphoma (B-NHL). CD81, a B-cell surface receptor, has been proposed as a receptor for HCV binding and entry in circulating B cells. The stimulation of CD81 complex enables B cells to respond to lower concentrations of antigen and finally induces B-cell proliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
(72 reference statements)
1
11
1
1
Order By: Relevance
“…The association between HCV-related immune disorders and the increase of CD5? B cells remains controversial [17][18][19][20]. In the present study, no significant differences were found in the frequencies of CD5?…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The association between HCV-related immune disorders and the increase of CD5? B cells remains controversial [17][18][19][20]. In the present study, no significant differences were found in the frequencies of CD5?…”
Section: Discussioncontrasting
confidence: 65%
“…While some authors reported increase of CD5? B cells in the patients with HCV or HCV-related cryoglobulinemia [17,18], others reported a lower expression of CD5 in patients with HCV-related lymphoproliferative disease [19], and others reported that no correlation was found between the increase of CD5? B cells and the presence of cryoprecipitate or rheumatoid factor (RF) in patients with HCV [20].…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneity may help to explain the discrepancies present in the literature regarding the phenotype of B cells clones in HCV infected individuals (4,(24)(25)(26)(27)(28). Accordingly, also a sizeable fraction of CD5 À MBL do exist in HCV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that in the course of HCV infection, B cell clones were mainly CD5 þ (4,24), although this has not been confirmed by others (25,26). CD5 À B cells have been reported to produce monoclonal IgM in MC (13,27,28).…”
mentioning
confidence: 96%
“…The stimulation of the CD81 complex enables B-cells to respond to lower concentrations of antigen and facilitates B-cell proliferation. 26 Finally, the t(14; 18) translocation has been shown to be present in a significant percentage of peripheral blood lymphocytes in HCV infected individuals, particularly with MC. 27 This translocation is responsible for BCL-2 activation, which extends B-cell survival by inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%